Gate‐Tunable Anisotropic Oxygen Ion Migration in SrCoOx: Toward Emerging Oxide‐Based Artificial Synapses. (18th January 2023) - Miao, Tingting; Cui, Bin; Huang, Cungang; Wang, Di; Liu, Long; Liu, Weikang; Li, Yongzhe; Chu, Ruiyue; Ren, Xue; Liu, Liang; Cheng, Bin; Zhou, Guangjun; et al.
Abstract : The construction of artificial synapse based on the electric field‐controlled ion migration has been developed to be a prospective approach to achieving intelligent devices with advantage of low‐energy consumption. However, it is still a very challenging task for artificial synapses to imitate the complex synapse diversity of biological system. Herein, the ionic liquid gating induced oxygen ion migration to realize the reversible phase transition between insulating SrCoO2.5 and metallic SrCoO3 with anisotropic dynamics due to the fast oxygen transport channel along [110] crystal orientation is used. The crystal orientation‐dependent oxygen ion migration and resultant metal–insulator transition offer an intriguing opportunity to build up a variety of artificial synapses with different performances, like excitatory or inhibitory characters, learning accuracy, and cooperation capability. Our findings not only give an insight into the anisotropic ion migration in oxides but also could be a fundamental step toward the development of diverse oxide‐based artificial neural networks. Abstract : Based on the anisotropic oxygen ion migration and resultant orientation‐dependent conductivity response, a variety of artificial synapses with different performances, like excitatory or inhibitory characters, learning accuracy, and cooperation capability, are built up. These results not only supply an insight into the dynamics of ion migration but also open a new avenue for synapse system with complex diversity.